Evaluación de los recursos turísticos para el desarrollo del turismo comunitario en la región costa norte de Manabí. - Lectong Vera, Jonathan Remigio (2018)
The objective of this research is to evaluate tourist resources for the development of community tourism in the north coast region of Manabi after the earthquake on April 16. The methodologies of Mori, 2008 were used as methodological antecedents; Pacheco et al., 2011; Herrera et al., 2014; Chavez and Bulnes, 2015 and Reyes et al., 2015, the research has a focus, exploratory, descriptive and explanatory. A methodological procedure was structured that counts on four phases, the first the tourist diagnosis identifying the damages caused by the earthquake in Pedernales, Jama, San Vicente and Bahía, was characterized by the analysis of relevant information of each canton (geography, economy, social and tourist). The second phase in the market study was identified that tourists who visit these cantons have preferences for natural sites, which are a potential within the territory. The evaluation of resources as a third phase allowed, through the data collection forms, to know that the attractions had serious effects on tourist facilities, infrastructure both lodging and catering amounting to $ 179,920.00. To identify the proposals for use as a last phase of research, an analysis (SWOT) was carried out, evaluating the positive and negative characteristics that contribute to the use and conservation of tourism potential; In addition, actions were established in the attractions such as repairs of establishments, designs of flora and fauna conservation products, improvement of tourist facilities and other proposals considered in the resources that were evaluated.